Effects of different external cooling placements prior to and during exercise on athletic performance in the heat: A systematic review and meta-analysis - Jiang, Dongting; Yu, Qiuyu; Liu, Meng; Dai, Jinjin (Frontiers in Physiology, 2023)
Background: Many high-profile international sport events are often held in warm or hot environments, hence, it is inevitable for these elite athletes to be prepared for the challenges from the heat. Owing to internal cooling may cause gastrointestinal discomfort to athletes, external cooling technique seems to be a more applicable method to deal with thermal stress. Central cooling mainly refers to head, face, neck and torso cooling, can help to reduce skin temperature and relieve thermal perception. Peripheral cooling mainly refers to four limbs cooling, can help to mitigate metabolic heat from muscular contraction to effectively prevent the accumulation of body heat. Hence, we performed a meta-analysis to assess the effectiveness of different external cooling placements on athletic performance in the heat. Methods: A literatures search was conducted using Web of Science, MEDLINE and SPORTDiscus until September 2022. The quality and risk of bias in the studies were independently assessed by two researchers. Results: 1430 articles were initially identified (Web of Science=775; MEDLINE=358; SPORTDiscus=271; Additional records identified through other sources=26), 60 articles met the inclusion criteria and were included in the final analysis, with overall article quality being deemed moderate. Central cooling (SMD = 0.43, 95% CI 0.27 to 0.58, p < 0.001) was most effective in improving athletic performance in the heat, followed by central & peripheral cooling (SMD = 0.38, 95% CI 0.23 to 0.54, p < 0.001), AND peripheral cooling (SMD = 0.32, 95% CI 0.07 to 0.57, p = 0.013). Conclusion: Central cooling appears to be an more effective intervention to enhance performance in hot conditions through improvements of skin temperature and thermal sensation, compared to other external cooling strategies. The enhancement effects of peripheral cooling require sufficient re-warming, otherwise it will be trivial. Although, central & peripheral cooling seems to retain advantages from central cooling, as many factors may influence the effects of peripheral cooling to offset the positive effects from central cooling, the question about whether central & peripheral cooling method is better than an isolated cooling technique needs more researchs to explore it.